G6f-like is an ITAM-containing collagen receptor in thrombocytes. - Craig E Hughes; Uvaraj P Radhakrishnan; Marie Lordkipanidzé; Stuart Egginton; Johannes M Dijkstra; Pudur Jagadeeswaran; Stephen P Watson (PLoS ONE)
Collagen activates mammalian platelets through a complex of the immunoglobulin (Ig) receptor GPVI and the Fc receptor γ-chain, which has an immunoreceptor tyrosine-based activation motif (ITAM). Cross-linking of GPVI mediates activation through the sequential activation of Src and Syk family kinases and activation of PLCγ2. Nucleated thrombocytes in fish are activated by collagen but lack an ortholog of GPVI. In this study we show that collagen activates trout thrombocytes in whole blood and under flow conditions through a Src kinase driven pathway. We identify the Ig receptor G6f-like as a collagen receptor and demonstrate in a cell line assay that it signals through its cytoplasmic ITAM. Using a morpholino for in vivo knock-down of G6f-like levels in zebrafish, we observed a marked delay or absence of occlusion of the venous and arterial systems in response to laser injury. Thus, G6f-like is a physiologically relevant collagen receptor in fish thrombocytes which signals through the same ITAM-based signalling pathway as mammalian GPVI, providing a novel example of convergent evolution.